Pengabdian Pembuatan Sumur Gali Dalam Menghindari Dampak Penambangan Emas Ilegal Terhadap Kesehatan Masyarakat Petapahan Barat Kuantan Singingi - Thamrin Thamrin; Mulyadi Mulyadi; Jonny Zain; Rahmadi Rahmadi; Desfi Yunarto (PELANTAR PRESS, 2022)
Recently, many people have carried out gold mining in various places. The mainland Riau area can mainly be found in almost all Kuantan Singingi district areas, but the mining type is classified as illegal (PETI). This service is carried out in Petapan Village from July to September 2021 to prevent the community from the impact of PETI mining. To overcome this, the initiator developed dug wells as an example for the economically disadvantaged community. The dug wells that are made have clean water, not the same as some of the existing dug wells.